Architecture of the Cutaneous Autonomic Nervous System - Glatte, Patrick; Buchmann, Sylvia J.; Hijazi, Mido Max; Illigens, Ben Min-Woo; Siepmann, Timo (Frontiers in Neurology, 2019)
Abstract The human skin is a highly specialized organ for receiving sensory information but also to preserve the body’s homeostasis. These functions are mediated by cutaneous small nerve fibers which display a complex anatomical architecture and are commonly classified into cutaneous A-beta, A-delta and C-fibers based on their diameter, myelinization and velocity of conduction of action potentials. Knowledge on structure and function of these nerve fibers is relevant as they are selectively targeted by various autonomic neuropathies such as diabetic neuropathy or Parkinson’s disease. Functional integrity of autonomic skin nerve fibers can be assessed by quantitative analysis of cutaneous responses to local pharmacological induction of axon reflex responses which result in dilation of cutaneous vessels, sweating or piloerection depending on the agent used to stimulate this neurogenic response. Sensory fibers can be assessed using quantitative sensory test. Complementing these functional assessments, immunohistochemical staining of superficial skin biopsies allow analysis of structural integrity of cutaneous nerve fibers, a technique which has gained attention due to its capacity of detecting pathogenic depositions of alpha-synuclein in patients with Parkinson’s disease. Here, we reviewed the current literature on the anatomy and functional pathways of the cutaneous autonomic nervous system as well as diagnostic techniques to assess its functional and structural integrity.